2013
DOI: 10.3819/ccbr.2013.80004
|View full text |Cite
|
Sign up to set email alerts
|

Animals prefer reinforcement that follows greater effort: Justification of effort or within-trial contrast?

Abstract: Justification of effort by humans is a form of reducing cognitive dissonance by enhancing the value of rewards when they are more difficult to obtain. Presumably, assigning greater value to rewards provides justification for the greater effort needed to obtain them. We have found such effects in adult humans and children with a highly controlled laboratory task. More importantly, under various conditions we have found similar effects in pigeons, animals not typically thought to need to justify their behavior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…For example, Aronson and Mills (1959) manipulated task difficult and reported that participants who were required to read some embarrassing sexual descriptions in order to join a discussion group placed greater value on the group as the severity of the required task increased. Recently, a similar phenomenon has been reported in nonhuman animals (Zentall, 2013). A series of studies beginning with Clement, Feltus, Kaiser, and Zentall (2000) has examined whether there are differences in preferences for outcomes that follow two kinds of preceding tasks involving different efforts.…”
mentioning
confidence: 54%
See 4 more Smart Citations
“…For example, Aronson and Mills (1959) manipulated task difficult and reported that participants who were required to read some embarrassing sexual descriptions in order to join a discussion group placed greater value on the group as the severity of the required task increased. Recently, a similar phenomenon has been reported in nonhuman animals (Zentall, 2013). A series of studies beginning with Clement, Feltus, Kaiser, and Zentall (2000) has examined whether there are differences in preferences for outcomes that follow two kinds of preceding tasks involving different efforts.…”
mentioning
confidence: 54%
“…They found that although the preference for the following stimuli became greater with increased amounts of training, the direction of the preference was inconsistent with the prediction based on the WTC. These studies have provided evidence about the boundary conditions of the WTC, and also gave rise to an argument about procedural variables (e.g., Zentall, 2013;Zentall & Singer, 2007). As one of the main procedural variables, the preceding tasks were not sufficiently aversive events for the individuals (Zentall, 2013).…”
mentioning
confidence: 93%
See 3 more Smart Citations